História da matemática e resolução de problemas: uma proposta de intervenção com problemas históricos - Vidal, Mariana de Macedo (2019)
The present work has as a theme the History of Mathematics and Problem Solving via historical problems, in order to analyze a proposal of intervention in workshop format that involved historical problems in mathematics teaching, developed in a group of 8th grade Elementary School New More Education Program, from a public school of the state network of the municipality of Mamanguape PB. Our intention was to answer the following question: What are the potentialities and limitations of the teaching proposal that links to historical problems in the teaching of Mathematics? We use as theoretical reference the works of Mendes (2006), Eves (2004), Brazil (1998), among others. As for the approach was a qualitative study, regarding the objectives was an exploratory research, which used the procedures of the case study. The subjects of the research were 16 students, from the 8th year of elementary school, of a Public School of the State Network of the Municipality of Mamanguape, Paraíba. The students' records, the evaluation questionnaire and the observation were used as instruments of data collection. The results indicate that the students presented a great difficulty in reading and interpreting the texts, demonstrated motivation and enthusiasm in the execution of the proposed activities and presented difficulties in interpreting a mathematical problem through a geometric representation. We conclude that the use of historical problems promotes students' interest in the study of mathematical content, encourages students to participate and to take a more active stance in mathematics classes; stimulates thinking mathematically, integrates the history of mathematics and solving problems with other resources.